2013
DOI: 10.1111/jspn.12037
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of parents and children regarding asthma management responsibilities

Abstract: It is important that nurses provide education and counseling to both children and their families to ensure that children take responsibility for disease management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…These findings are consistent with international studies, indicating that school-age children aged ≥8 years can develop asthma self-management skills [10,13,16,22]. This ability to take responsibility for asthma management is likely to result from developmental changes.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings are consistent with international studies, indicating that school-age children aged ≥8 years can develop asthma self-management skills [10,13,16,22]. This ability to take responsibility for asthma management is likely to result from developmental changes.…”
Section: Discussionsupporting
confidence: 89%
“…This study follows that theory because it shows that managing asthma requires family support. Between the ages of 7 and 12, the role of parents must be transitioned from controlling guardians to gentle supporters [13]. Findings from this study indicated that family support encouraged children's active engagement with self-management behaviors through teaching them about the use of inhalers, as well as supervising them to be responsible for their own medicine management.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…12 13 The answer to this problem lies in shared asthma management by the parent-child dyad, 12 13 with the school-age years the ideal developmental period for children to begin sharing responsibility with their parents and establishing lifelong health behaviours. [22][23][24][25] Using a Human-Centred Design framework, we collaborated with parent-child dyads to codesign Improving Asthma Care Together (IMPACT), a tailored shared management mobile health (mHealth) application that pairs the parent and child together as a shared management team. 26 27 IMPACT aims to help families tailor asthma management strategies to fit the realities of their social environments while facilitating intentional transition of asthma management to the child.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…If the elementary student self-carried, the nurses still wanted to be included, informed, and able to assess the student after each inhaler use, professedly for documentation and assessment purposes. This finding was supported by Ekim and Ocakci's (2013) study recommending that nurses continue to supervise and be involved in a child's care even as children increase their own self-care. Elementary school nurses believed that students who managed their asthma and self-carried had increased exacerbations and 9-1-1 calls due to overmedicating, pushing themselves, or forgotten medications.…”
Section: Manipulationmentioning
confidence: 79%